Gastroenteritis - Walker-Smith, John (Diseases of the Small Intestine in Childhood, 1988)
Acute gastroenteritis is an infectious disease of the alimentary tract that may be caused by one or more bacterial, viral, or protozoal pathogens producing damage, either structural or functional, of variable extent and severity to the mucosa. Acute gastroenteritis is a very common diagnosis in pediatric practices. It is usually a clinical diagnosis. Its most common symptoms are acute vomiting and diarrhea. The most important acute complication of gastroenteritis is dehydration, which occurs when the child's overall output of fluid exceeds input. Insensible water loss is the volume of fluid that leaves the body as a result of the difference in vapor pressure between the skin and lung surfaces and the surrounding atmosphere. The small intestine is the organ principally affected in most children by gastroenteritis but the stomach and colon may also be involved to a varying extent. Most often acute gastroenteritis is a self-limiting illness and may result in full recovery after 24 hours.